Overcoming Major Environmental and Production Challenges in Cattle Owned by Smallholder Farmers in the Tropics - Heather M. Burrow (Universitas Sebelas Maret, 2022)
The world’s population is expected to increase significantly by 2050, leading to significantly increased demands for meat and dairy products. However, cattle are major emitters of greenhouse gases that speed up climate change. To achieve food security by 2050, livestock enterprises need to double their outputs from constant resources, in the face of increased competition for inputs such as land, water, grain and labour. To cope with climate change, the livestock need to be productive under hotter and drier climates and be able to tolerate increased challenges from parasites and vector-borne diseases. The best way for smallholder cattle farmers in tropical low-medium income countries to overcome these multiple challenges is to focus on improving the productivity of their herds. This paper discusses a range of simple and cost-effective options already available to smallholder farmers to significantly improve the productivity and profitability of their herds and by doing so, they will indirectly reduce greenhouse gas emissions from their cattle and improve the natural resource base on which their cattle graze. Improved herd productivity will in turn deliver significant social, environmental, economic and livelihood benefits to the smallholder farmers themselves and the communities and value chains in which they operate.